(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
A train of thought prompted by the key conference question is followed down a rabbit hole, finding Colin Wilson, author of The Outsider and a New Existentialism, and eventually emerging as a potential book outline on the state of existentialism in the current European context.